High-Throughput Analysis of the T Cell Receptor Beta Chain Repertoire in PBMCs from Chronic Hepatitis B Patients with HBeAg Seroconversion. (13th October 2016) - Qu, Yachao; Huang, Yong; Liu, Di; Huang, Yinuo; Zhang, Zhiyi; Mi, Zhiqiang; An, Xiaoping; Tong, Yigang; Lu, Jun
Abstract : T lymphocytes are the most important immune cells that affect both the development and treatment of hepatitis B. We used high-throughput sequencing to determine the diversity in the V and J regions of the TCR β chain in 4 chronic hepatitis B patients before and after HBeAg seroconversion. Here, we demonstrate that the 4 patients expressedV β 12 -4 at the highest frequencies of 10.6%, 9.2%, 17.5%, and 7.5%, andV β 28 was the second most common, with frequencies of 7.8%, 6.7%, 5.3%, and 10.9%, respectively. No significant changes were observed following seroconversion. With regard to the J β gene, J β 2-1 was the most commonly expressed in the 4 patients at frequencies of 5.8%, 6.5%, 11.3%, and 7.3%, respectively. Analysis of the V-J region genes revealed several differences, including significant increases in the expression levels of V7-2-01-J2-1, V12-4-J1-1, and V28-1-J1-5 and a decrease in that of V19-01-J2-3. These results illustrate the presence of biased TCRV β and J β gene expression in the chronic hepatitis B patients. TRBV β 12-4, V β 28, J β 2-1, V7-2-01-J2-1, V12-4-J1-1, and V28-1-J1-5 may be associated with the development and treatment of CHB.